PlanHab*: hypoxia does not worsen the impairment of skeletal muscle oxidative function induced by bed rest alone. (17th April 2018) - Salvadego, Desy; Keramidas, Michail E.; Kölegård, Roger; Brocca, Lorenza; Lazzer, Stefano; Mavelli, Irene; Rittweger, Jörn; Eiken, Ola; Mekjavic, Igor B.; Grassi, Bruno
Abstract : Key points: Superposition of hypoxia on 21 day bed rest did not worsen the impairment of skeletal muscle oxidative function induced by bed rest alone. A significant impairment of maximal oxidative performance was identified downstream of cardiovascular O2 delivery, involving both the intramuscular matching between O2 supply and utilization and mitochondrial respiration. These chronic adaptations appear to be relevant in terms of exposure to spaceflights and reduced gravity habitats (Moon or Mars), as characterized by low gravity and hypoxia, in patients with chronic diseases characterized by hypomobility/immobility and hypoxia, as well as in ageing. Abstract: Skeletal muscle oxidative function was evaluated in 11 healthy males (mean ± SD age 27 ± 5 years) prior to (baseline data collection, BDC) and following a 21 day horizontal bed rest (BR), carried out in normoxia ( P I O 2  = 133 mmHg; N‐BR) and hypoxia ( P I O 2  = 90 mmHg; H‐BR). H‐BR was aimed at simulating reduced gravity habitats. The effects of a 21 day hypoxic ambulatory confinement ( P I O 2  = 90 mmHg; H‐AMB) were also assessed. Pulmonary O2 uptake ( V ̇ O 2 ), vastus lateralis fractional O2 extraction (changes in deoxygenated haemoglobin + myoglobin concentration, Δ[deoxy(Hb + Mb)]; near‐infrared spectroscopy) and femoral artery blood flow (ultrasound Doppler) were evaluated during incremental one‐leg knee‐extension exercise (reduced constraints to cardiovascular O2 delivery) carried out to voluntary exhaustion in a normoxic environment. Mitochondrial respiration was evaluated ex vivo by high‐resolution respirometry in permeabilized vastus lateralis fibres. V ̇ O 2 peak decreased ( P  < 0.05) after N‐BR (0.98 ± 0.13 L min −1 ) and H‐BR (0.96 ± 0.17 L min −1 ) vs . BDC (1.05 ± 0.14 L min −1 ). In the presence of a decreased (by ∼6–8%) thigh muscle volume, V ̇ O 2 peak normalized per unit of muscle mass was not affected by both interventions. Δ[deoxy(Hb + Mb)]peak decreased ( P  < 0.05) after N‐BR (65 ± 13% of limb ischaemia) and H‐BR (62 ± 12%) vs . BDC (73 ± 13%). H‐AMB did not alter V ̇ O 2 peak or Δ[deoxy(Hb + Mb)]peak . An overshoot of Δ[deoxy(Hb + Mb)] was evident during the first minute of unloaded exercise after N‐BR and H‐BR. Arterial blood flow to the lower limb during both unloaded and peak knee extension was not affected by any intervention. Maximal ADP‐stimulated mitochondrial respiration decreased ( P  < 0.05) after all interventions vs . control. In 21 day N‐BR, a significant impairment of oxidative metabolism occurred downstream of cardiovascular O2 delivery, affecting both mitochondrial respiration and presumably the intramuscular matching between O2 supply and utilization. Superposition of H on BR did not worsen the impairment induced by BR alone. Key points: Superposition of hypoxia on 21 day bed rest did not worsen the impairment of skeletal muscle oxidative function induced by bed rest alone. A significant impairment of maximal oxidative performance was identified downstream of cardiovascular O2 delivery, involving both the intramuscular matching between O2 supply and utilization and mitochondrial respiration. These chronic adaptations appear to be relevant in terms of exposure to spaceflights and reduced gravity habitats (Moon or Mars), as characterized by low gravity and hypoxia, in patients with chronic diseases characterized by hypomobility/immobility and hypoxia, as well as in ageing.